2019
DOI: 10.1136/openhrt-2018-000926
|View full text |Cite
|
Sign up to set email alerts
|

Native aortic versus mitral valve infective endocarditis: a nationwide registry study

Abstract: BackgroundNative aortic and mitral valve infective endocarditis (AVE and MVE, respectively) are usually grouped together as left-sided native valve infective endocarditis (LNVE), while the differences between AVE and MVE have not yet been properly investigated. We aimed to compare AVE and MVE in regard to patient characteristics, microbiology and determinants of survival.MethodsWe conducted a retrospective study using the Swedish national registry on infective endocarditis, which contains nationwide patient da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…When grouping patients according to localization of IE, we found that males more commonly had an aortic localization, while females predominantly had mitral localization of infection. The same has previously been documented in studies on native IE [7].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…When grouping patients according to localization of IE, we found that males more commonly had an aortic localization, while females predominantly had mitral localization of infection. The same has previously been documented in studies on native IE [7].…”
Section: Discussionsupporting
confidence: 78%
“…One report that investigated PVE caused by S. aureus found the risk of S. aureus as the etiologic agent was similar in patients with late and early PVE and infection localization on mechanical and bioprosthetic valves [6]. A previous study based on the Swedish Registry on Infective Endocarditis (SRIE) focusing on NVE found that S. aureus was more commonly a causative pathogen affecting the mitral valve (41% vs. 31%, p < 0.001), whereas enterococci and CoNS were more prone to engage the aortic valve [7].…”
Section: Introductionmentioning
confidence: 99%
“…The registry has been used to present clinical data regarding various pathogens [27][28][29][30][31][32] and has made contributions to numerous studies within the framework of the International Collaboration on Endocarditis (ICE) with around 30 publications [3,6,33].…”
Section: Sources Of Datamentioning
confidence: 99%
“… [3] Among left-sided native valve infective endocarditis, mitral valve IE (MVE) is more common than aortic valve IE (AVE). Staphylococcus aureus is most commonly associated with MVE [4] .…”
Section: Introductionmentioning
confidence: 99%